#### Answer

$x^{2}$ - 5x -14 = (x+2)(x-7)

#### Work Step by Step

$x^{2}$ - 5x -14 = (x+2) (x__)
step 1. Enter x as the first term of each factor
$x^{2}$ - 5x -14 = (x+2) (x__)
Step 2. To find the second term of each factor, we must find two integers whose product is -14 and whose sum is -5
List pairs of factors of the constant, -30
(1,-14)(-1,14)(-2,7),(2,-7)
step 3. The correct factorization of $x^{2}$ - 5x -14 is the one in which the sum of the Outside and Inside products is equal to -5.
So (2,-7) satisfy the condition
$x^{2}$ - 5x -14 = $x^{2}$ + 2x -7x - 14 = (x+2)(x-7)